TIM-3, LAG-3, or 2B4 gene disruptions increase the anti-tumor response of engineered T cells - Cianciotti, Beatrice Claudia; Magnani, Zulma Irene; Ugolini, Alessia; Camisa, Barbara; Merelli, Ivan; Vavassori, Valentina; Potenza, Alessia; Imparato, Antonio; Manfredi, Francesco; Abbati, Danilo; Perani, Laura; Spinelli, Antonello; et al. (Frontiers in Immunology, 2024)
Background In adoptive T cell therapy, the long term therapeutic benefits in patients treated with engineered tumor specific T cells are limited by the lack of long term persistence of the infused cellular products and by the immunosuppressive mechanisms active in the tumor microenvironment. Exhausted T cells infiltrating the tumor are characterized by loss of effector functions triggered by multiple inhibitory receptors (IRs). In patients, IR blockade reverts T cell exhaustion but has low selectivity, potentially unleashing autoreactive clones and resulting in clinical autoimmune side effects. Furthermore, loss of long term protective immunity in cell therapy has been ascribed to the effector memory phenotype of the infused cells. Methods We simultaneously redirected T cell specificity towards the NY-ESO-1 antigen via TCR gene editing (TCRED) and permanently disrupted LAG3, TIM-3 or 2B4 genes (IRKO) via CRISPR/Cas9 in a protocol to expand early differentiated long-living memory stem T cells. The effector functions of the TCRED-IRKO and IR competent (TCRED-IRCOMP) cells were tested in short-term co-culture assays and under a chronic stimulation setting in vitro. Finally, the therapeutic efficacy of the developed cellular products were evaluated in multiple myeloma xenograft models. Results We show that upon chronic stimulation, TCRED-IRKO cells are superior to TCRED-IRCOMP cells in resisting functional exhaustion through different mechanisms and efficiently eliminate cancer cells upon tumor re-challenge in vivo. Our data indicate that TIM-3 and 2B4-disruption preserve T-cell degranulation capacity, while LAG-3 disruption prevents the upregulation of additional inhibitory receptors in T cells. Conclusion These results highlight that TIM-3, LAG-3, and 2B4 disruptions increase the therapeutic benefit of tumor specific cellular products and suggest distinct, non-redundant roles for IRs in anti-tumor responses.